Optimum Design of Hammer Mill for Grinding Leonardite - Promdan, Surapin; Panananda, Nuttarut; Munsin, Ronnachart; Chaichana, Suphamat; Yeunyongkul, Pracha; Khrabunma, Supol (Journal of Technical Education Science, 2023)
The objective of this research is to design and construct a hammer mill for grinding leonardite charcoal (Lignite, class J). The conditions for the design and construction of the grinder are hammer thickness, 3, 6, and 9 mm, a number, hammer 20, 24, and 28. The size of the ground leonardite should range between 250 mm to 30 mm (less than 0.066 mm). The hammer thickness and number of hammers were chosen alternatingly in order to see the effect of these two parameters. By manipulating these two parameters, it was found that the optimum operation can be achieved by using 28 hammers having a thickness of 3 mm. It results in the highest grinding efficiency of 96.2 percent. Percentages of the grate (retained) and passed of the ground mineral are found for each sieve size by means of weight. The approximations of the retained and passed were calculated and found to intersect at 225 mm. At the intersection, the percentage by weight passed through the sieve is 50 percent and the percentage by weight retained sieve is 50 percent, respectively.